Sports-Old campus-Womens baseball 001 (1917)
Senior girls' baseball team Back row(L to R) Lena Jensen, Wini fred Weage, Marcia Alghren, Grace Mitchell, Queenie Smale, Hellen Klaus, Front Row:Sybil McNeil, Louise Moglia, Eleanor Zimmerman, Clara Gribble, Captain; Henrietta Ellis, Manager; Gertrude Rasmussen